Influence of Organic Manures and Biofertilizers on Rhizome Quality of Arrowroot Intercropped in Coconut - Swadija, O.K.; VB, Padmanabhan; ., Vijayaraghavakumar (JOURNAL OF ROOT CROPS, 2015)
West Indian arrowroot (Maranta arundinacea L.) is an under-exploited tuber crop which is valued as a food stuff as well as source of starch. The starch is used for the preparation of various bakery products, as a base for face powder, in the preparation of barium meals and as a base for tablets, where rapid disintegration is desirable. The starch possesses demulscent and anti-diarrhoeal properties and is used in the treatment of intestinal disorders, which adds medicinal value to the crop. Presently organic farming assumes special significance due to environmental concern and food safety issues. There is dearth of information on the effect of organic management on yield and quality in arrowroot. Hence field experiments were conducted during 2007-2009 in the identified panchayats in the Western Ghat region of Thiruvananthapuram, Kerala, India, to derive an organic nutrient package for sustained yield of arrowroot. As part of the investigation, the effect of organic manures, at various levels with and without biofertilizers, on rhizome quality of arrowroot intercropped in coconut was studied in randomized block design at five locations, with three replications at each location. The results indicated that the quality characters of rhizomes, dry matter, starch, crude protein and crude fibre contents improved during both the years due to application of even 10 t ha-1 of farmyard manure. The study indicated the sufficiency of 15 t ha-1 of farmyard manure along with biofertilzers (Azospirillum and phosphobacteria) for realizing higher rhizome yield and improved rhizome quality of arrowroot intercropped in coconut.